Forensic Sciences Code of Ethics and Conduct: A Mere Formality or Imperative of the Modern Society - O. Miklyaeva (Теория и практика судебной экспертизы, 2014)
The paper examines the moral and ethical principles of the forensic profession andprospects for their legal codification, as well as the need to build a professional codeof ethics for forensic scientists and its potential practical significance.